Power Relations and Ideology in Islamic Education: A Political Analysis of Islamic Education in Indonesia - La Zubair (Suria Academic Press, 2026)
Islamic education is often in a dilemmatic position because it has to deal with various political interests of the state. This study aims to examine the relationship between power and ideology in Islamic education and its implications for Islamic education policies and practices. The method used is a qualitative approach with a type of literature study. The research findings show that the research findings show that there is a dialectical relationship between power and ideology in Islamic education in Indonesia which is complex and dynamic. This has implications for Islamic education policies, especially in the aspects of curriculum, regulations, and institutions. In addition, it also has implications for the practice of Islamic education at the micro level, especially in the learning process in the classroom. There are two main trends in learning orientation, namely normative orientation and pragmatic orientation. Thus, Islamic education is expected not only to be the object of power relations, but also to be able to play a role as a critical, reflective, and constructive subject of social transformation in building a civilized and just society.